2004
DOI: 10.1111/j.0886-0440.2004.04042.x
|View full text |Cite
|
Sign up to set email alerts
|

Off‐Pump Versus On‐Pump Reoperative CABG Via a Left Thoracotomy for Circumflex Coronary Artery Revascularization

Abstract: RCLT is an effective and safe approach for circumflex artery revascularization with excellent short- and mid-term results using either technique. The OPCAB technique is associated with reduced blood product utilization and shorter ICU and hospital length of stay and, therefore, is more cost-effective.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
14
0

Year Published

2008
2008
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 12 publications
(14 citation statements)
references
References 17 publications
0
14
0
Order By: Relevance
“…The 21 studies regarding off-pump versus on-pump in patients undergoing redo coronary surgery were included in the final analysis. 18,19,[36][37][38][39][40][41][42][43][44][45][46][47][48][49][50][51][52][53][54] Comprehensive search using the terms had been performed in November 2012 and May 2013 by the previous two meta-analysis, but the inclusion and exclusion criteria in our study were stricter than those used in the previous studies. 29,30 Even though the previous two studies included 12 articles, 18,43,[44][45][46][49][50][51][52][53][54][55] one study 47 that was missed and eight studies 19,[36][37][38][39][40][41][42] published after May 2013 were included in this study.…”
Section: Characteristics Of the Included Studiesmentioning
confidence: 99%
See 1 more Smart Citation
“…The 21 studies regarding off-pump versus on-pump in patients undergoing redo coronary surgery were included in the final analysis. 18,19,[36][37][38][39][40][41][42][43][44][45][46][47][48][49][50][51][52][53][54] Comprehensive search using the terms had been performed in November 2012 and May 2013 by the previous two meta-analysis, but the inclusion and exclusion criteria in our study were stricter than those used in the previous studies. 29,30 Even though the previous two studies included 12 articles, 18,43,[44][45][46][49][50][51][52][53][54][55] one study 47 that was missed and eight studies 19,[36][37][38][39][40][41][42] published after May 2013 were included in this study.…”
Section: Characteristics Of the Included Studiesmentioning
confidence: 99%
“…18,19,[36][37][38][39][40][41][42][43][44][45][46][47][48][49][50][51][52][53][54] Comprehensive search using the terms had been performed in November 2012 and May 2013 by the previous two meta-analysis, but the inclusion and exclusion criteria in our study were stricter than those used in the previous studies. 29,30 Even though the previous two studies included 12 articles, 18,43,[44][45][46][49][50][51][52][53][54][55] one study 47 that was missed and eight studies 19,[36][37][38][39][40][41][42] published after May 2013 were included in this study. Besides, Alamanni's study was not included in our metaanalysis for the reason of only reporting off-pump redo coronary artery bypass grafting results.…”
Section: Characteristics Of the Included Studiesmentioning
confidence: 99%
“…Twenty-one ( 21) studies consistently reported data regarding perioperative mortality data [10,[21][22][23][25][26][27][28][29][31][32][33][34][35][36][37][38][39][40][41][42]. The 30day mortality rate was 3.4% (n=68/2,024) and 7.4% (n=238/ 3,225) in the OPCAB and ONCAB repeat CABG groups, respectively.…”
Section: Periprocedural (Within 30 Days) Outcomesmentioning
confidence: 97%
“…The advent of peripheral cannulation techniques and endoluminal aortic occlusion balloons has allowed MIDCAB to be performed either on-or off-pump. Clinical studies have demonstrated that this procedure can be performed safely, with limited morbidity and mortality, under both native and re-operative situations (78)(79)(80)(81). Preliminary studies suggest excellent long-term patency of grafts following MIDCAB.…”
Section: Minimally Invasive and Robotic Coronary Revascularizationmentioning
confidence: 99%